Development of Integrated Physics Learning Videos for Tsunami Disaster Education to Increase Awareness and Preparedness of High School Students in Coastal Areas of Kulon Progo Regency - Sudrajad, Bangkit; Dwisiwi Sri Retnowati, Rahayu (Prodi Fisika FKIP Unram, 2023)
Students' awareness and preparedness for tsunami disasters are two very important things to minimize the impact of disasters, especially for those who live in coastal areas. This study aims to produce video media for learning physics that is integrated with tsunami disaster education that is suitable for use in helping students understand physics material while increasing awareness and preparedness of students in the coastal areas of Kulon Progo Regency against the tsunami disaster. The method used in this study is research and development with a 4D model (Define, Design, Develop, and Disseminate). At the define stage, defining and determining the needs in making learning videos; then in the design stage the initial product design of video media and learning tools is carried out, the develop stage is carried out by validating video media by expert and practitioner validators as well as product trials on high school students in the coastal area of Kulon Progo district; and finally, the disseminate stage is the dissemination of the final product to the internet network and to the school where the research is being carried out. The resulting physics learning video media is integrated with tsunami disaster education which is suitable for use in physics learning and can help understand business and energy material while increasing students' awareness and preparedness for tsunami disasters. Keywords: Learning Video; Tsunami; Disaster Education; Research and Development.